Lifestyle, personal well-being, and perception of parents by children of OFWs - Navales, Michael Duane D. (2009.)
Fifty-two(52) students from Iloilo National High School, with one or both parents working abroad for at least one year, were chosen through convenient sampling technique and were tested and interviewed., The researchers utilized a battery of tests and questionnaire to study the variables under investigation. It was found out that despite the physical absence of parents, children of OFWs were still able to maintain a healthy and safe lifestyle. Results also show that the respondents have high level of over-all personal well-being, and hold a positive perception of their parents.
Research Project (Undergraduate, Bachelor of Arts in Psychology-Management) College of Arts and Sciences, UP Visayas, Miagao, Iloilo
Keywords: Children of OFWs